Genetic modulation of islet β-cell iPLA(2)β expression provides evidence for its impact on β-cell apoptosis and autophagy - Lei, Xiaoyong (Landes Bioscience, 2013)
β-cell apoptosis is a significant contributor to β-cell dysfunction in diabetes and ER stress is among the factors that contributes to β-cell death. We previously identified that the Ca(2+)-independent phospholipase A(2)β (iPLA(2)β), which in islets is localized in β-cells, participates in ER stress-induced β-cell apoptosis. Here, direct assessment of iPLA(2)β role was made using β-cell-specific iPLA(2)β overexpressing (RIP-iPLA(2)β-Tg) and globally iPLA(2)β-deficient (iPLA(2)β-KO) mice. Islets from Tg, but not KO, express higher islet iPLA(2)β and neutral sphingomyelinase, decrease in sphingomyelins, and increase in ceramides, relative to WT group. ER stress induces iPLA(2)β, ER stress factors, loss of mitochondrial membrane potential (∆Ψ), caspase-3 activation, and β-cell apoptosis in the WT and these are all amplified in the Tg group. Surprisingly, β-cells apoptosis while reduced in the KO is higher than in the WT group. This, however, was not accompanied by greater caspase-3 activation but with larger loss of ∆Ψ, suggesting that iPLA(2)β deficiency impacts mitochondrial membrane integrity and causes apoptosis by a caspase-independent manner. Further, autophagy, as reflected by LC3-II accumulation, is increased in Tg and decreased in KO, relative to WT. Our findings suggest that (1) iPLA(2)β impacts upstream (UPR) and downstream (ceramide generation and mitochondrial) pathways in β-cells and (2) both over- or under-expression of iPLA(2)β is deleterious to the β-cells. Further, we present for the first time evidence for potential regulation of autophagy by iPLA(2)β in islet β-cells. These findings support the hypothesis that iPLA(2)β induction under stress, as in diabetes, is a key component to amplifying β-cell death processes.